Stress–strain behavior of a silty soil reinforced with polyethylene terephthalate (PET). Issue 4 (August 2015) - Botero, E.; Ossa, A.; Sherwell, G.; Ovando-Shelley, E.
Abstract In some cases, the production of solid waste is experiencing an uncontrolled and continuous increase, especially wastes from plastic products. Therefore, this study proposes an alternative reuse method for certain types of plastic waste (bottles and containers used for liquid storage that are processed using discrete fibers) in geotechnical construction projects. To this end, discrete polyethylene terephthalate (PET) fibers were randomly mixed with fine soil to modify their mechanical properties. The principal objective of this research was to study the mechanical behavior of a silty soil that was reinforced with aleatorily distributed PET fibers. To meet this objective, UU triaxial laboratory tests were performed on soil specimens with fiber contents of 0.0–1.0% of the soil dry weight. The test results indicated that the reinforced specimens presented an increment of shear strength that was associated with the increasing quantities of the PET fiber. Furthermore, the laboratory tests indicated that the reinforced soil had a greater deformation capacity, which can be a positive characteristic in some cases because the deformation capacity can reduce the risk of crack formation in certain soil layers for specific geotechnical problems. Finally, this reinforced soil presents interesting mechanical properties and could be used in structures that require a high deformation capacity, such as landfills, sewage treatment deposits and dams (among other uses), to prevent failures due to cracking and to prevent the possible leakage of contaminants or water. However, these issues are beyond the scope of this paper.